2020
DOI: 10.1136/archdischild-2020-319804
|View full text |Cite
|
Sign up to set email alerts
|

Supraglottic airway devices for administration of surfactant to newborn infants with respiratory distress syndrome: a narrative review

Abstract: Surfactant is an effective treatment for respiratory distress syndrome, being particularly important for infants in whom continuous positive airway pressure (CPAP) provides insufficient support. Supraglottic airway devices present an attractive option for surfactant delivery, particularly as an alternative to methods dependent on direct laryngoscopy, a procedural skill that is both difficult to learn and in which to maintain competence. Published studies provide encouraging data that surfactant administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Serios adverse events observed during surfactant administration via LMA include physiological instability during the procedure (prolonged bradycardia and/or desaturation), need for emergent intubation, tension pneumothorax, and PH. 93 However, many studies have reported no serious side effects during and after intervention. 86,88,[90][91][92][93] Supraglottic airway devices are suitable alternatives for surfactant administration, eliminating the need for direct laryngoscopy, and many studies have shown encouraging results.…”
Section: Surfactant Administration Via Lmamentioning
confidence: 99%
See 1 more Smart Citation
“…Serios adverse events observed during surfactant administration via LMA include physiological instability during the procedure (prolonged bradycardia and/or desaturation), need for emergent intubation, tension pneumothorax, and PH. 93 However, many studies have reported no serious side effects during and after intervention. 86,88,[90][91][92][93] Supraglottic airway devices are suitable alternatives for surfactant administration, eliminating the need for direct laryngoscopy, and many studies have shown encouraging results.…”
Section: Surfactant Administration Via Lmamentioning
confidence: 99%
“…93 However, many studies have reported no serious side effects during and after intervention. 86,88,[90][91][92][93] Supraglottic airway devices are suitable alternatives for surfactant administration, eliminating the need for direct laryngoscopy, and many studies have shown encouraging results. However, the studies till date have heterogenous study design and a small number of subjects.…”
Section: Surfactant Administration Via Lmamentioning
confidence: 99%
“…The possible bene ts of utilizing SAD over LISA are ease of placement and minimization of potential complications of intubation including oxygen desaturation, bradycardia, changes in blood pressure that may increase the risk of intracranial hemorrhage, and trauma to the oropharyngeal tissue. 2,4,[6][7][8] In contrast, LISA requires at least the same skills as intubation and carries similar risks including transient hypoxemia and bradycardia with possible changes in cerebral perfusion rates. [6][7][8][9][10][11][12][13][14] During LISA, positive pressure ventilation (PPV) can be potentially avoided whereas with SAD, PPV is still required to instill the surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…During both methods, infants can remain on a non-invasive ventilation (NIV) mode. [1][2][3][4][5] Currently available sizes of SAD devices limit the application of this procedure to birth weights > 1000g, with the smallest infant reported having a birth weight of 1050g. 2,16 Unfortunately, prior randomized controlled trials (RCTs) on surfactant delivery by SAD have been heterogeneous in entry criteria, ranges of gestational age and birth weight, different premedication protocols and used various SAD devices.…”
Section: Introductionmentioning
confidence: 99%
“…Besides nebulization [13,14], another proposed mode for surfactant delivery in preterm infants is the use of a laryngeal mask airway (LMA) [15,16], a supraglottic airway device. This technique's advantage is reducing invasiveness by precluding laryngoscopy during catheter positioning and requiring less training for proper placement than laryngoscopy and endotracheal intubation.…”
Section: Introductionmentioning
confidence: 99%